Report on a study to crowdsource farmgate prices for maize and soybeans in Malawi - Ochieng, Dennis O.; Baulch, Bob (International Food Policy Research Institute, 2020)
This report summarizes the findings from an innovative study to collect the prices that farmers received for maize and soybeans during the 2020 main marketing season in Malawi. Between April and July, whenever they sold maize or soybeans, farmers were asked to report the prices they received by calling or texting a toll-free number managed by Farm Radio Trust. Reported prices were then compared to the minimum farmgate prices set by the Ministry of Agriculture and Food Security. Our findings show that 75 percent of maize farmers and 90 percent of soybean farmers sold their crops below the official minimum farmgate prices. On average, prices received by these farmers were approximately three-quarters of official minimum farmgate prices.